2002
DOI: 10.1046/j.1440-1827.2002.01331.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of cell damage in Helicobacter pylori‐associated gastritis

Abstract: Helicobacter pylori infection is currently considered to be a major cause of acute and chronic gastritis, and of gastric and duodenal ulcers. Superoxide dismutase (SOD) is well known for scavenging superoxide radicals such as reactive oxygen species (ROS), subsequently protecting cells from oxidative injury, and for maintaining tissue homeostasis. In this study, we therefore evaluated the level of SOD activity and protein expression, as well as various factors associated with oxidative injury, in H. pylori-pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…Noguchi et al[174] reported that Mn-SOD immunoreactivity was present in CD68-positive macrophages adjacent to the neck of the foveolar glands, and that the level of Mn-SOD protein showed a significant correlation with the degree of inflammation in the gastric mucosa. Vitamin C is actively secreted into and concentrated within the gastric juice of the healthy stomach.…”
Section: Reactive Oxygen and Nitrogen Speciesmentioning
confidence: 99%
“…Noguchi et al[174] reported that Mn-SOD immunoreactivity was present in CD68-positive macrophages adjacent to the neck of the foveolar glands, and that the level of Mn-SOD protein showed a significant correlation with the degree of inflammation in the gastric mucosa. Vitamin C is actively secreted into and concentrated within the gastric juice of the healthy stomach.…”
Section: Reactive Oxygen and Nitrogen Speciesmentioning
confidence: 99%
“…Gotz et al first reported an increase of Mn-SOD in H. pylori -positive gastric mucosa. The study showed a significant correlation between the level of Mn-SOD protein with the degree of inflammation in the gastric mucosa (Noguchi et al, 2002;Smoot et al, 2000). Recently, we have reviewed the important role of Mn-SOD in inflammation (Dovhanj et al, 2010).…”
Section: Role Of Glutathione and Mn-sod In Oxidative Stress -Induced mentioning
confidence: 95%
“…However, we found two somatic mutations in hydrolase domain of the MYH gene. Several observations support the possibility that defective MYH enzyme could result in the development of gastric cancer; (1) the gastrointestinal tract is constantly subject to traumas from ingested food particles and various noxious agents, including H. pylori; (2) H. pylori infection is the single most important factor in high frequency of oxidative DNA damage; (3) levels of 8-oxoG was significantly higher in H. pylori-positive gastric mucosa than in negative tissues (Noguchi et al, 2002); (4) inherited defects of the MYH predispose to multiple colorectal adenomas and carcinoma (Jones et al, 2002;Sieber et al, 2003); (5) It has been expected that B1-3% of all colorectal cancers would result from MYH change (Halford et al, 2003). In this study, somatic mutations of the MYH were found in 2.1% of gastric cancer; and (6) Gastric cancer was developed in the patients with inherited mutation of MYH gene .…”
mentioning
confidence: 89%
“…Of these, the DNA glycosylase mutY excises adenine misincorporated opposite unrepaired 8-oxoG during replication (Lindahl, 1993). Interestingly, increased level of 8-oxoG was frequently seen in H. pylori-associated gastritis and several human cancers, including lung cancers, breast cancers and renal cell carcinoma (Malins and Haimanot, 1991;Jaruga et al, 1994;Okamoto et al, 1994;Noguchi et al, 2002). Thus, we hypothesized that the deficiencies of base excision repair pathway cause transversion mutations caused by reactive oxygen species and that they play an important role in the development of human cancer.…”
mentioning
confidence: 99%